Mechanical behavior and optimization of multidirectional laminate specimens under delamination by bending - Ahmed Benyahia, A.; Laksimi, A.; Ouali, N.; Azari, Z. (Проблемы прочности, 2006)
Delamination in the multidirectional laminates under bending loading is often difficult to characterize because of problems involved by excessive deformations ahead of the crack tip and by non-linearities due to large displacements and transverse microcracking. In fact, these microcracks appear in the most strained plies especially for thin materials. Consequently, the concept of linear elastic fracture mechanic cannot be used in order to characterize delamination. Thus, the objective of this work is to highlight, experimentally and analytically these problems on DCB specimens, then to carry out optimization of thickness which makes it possible to avoid the appearance of transverse cracking before starting of delamination. The material used is E-glass/epoxy multidirectional laminates. The results of optimization obtained are in good agreement with the experimental results.